Etika Evaluasi, Penilaian, dan Objektivitas dalam Pendidikan - Nelly Hastuti; Haris Riadi; Najma Qurrotul ‘Aini (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Evaluation and assessment are fundamental components of the educational process, serving to measure students’ learning outcomes and to support instructional decision-making. In practice, evaluation is not merely technical but must also be grounded in ethical principles to ensure that assessment results accurately reflect students’ actual abilities. This study aims to examine the importance of ethics in educational evaluation, focusing on the principles of objectivity, fairness, and honesty as forms of teachers’ moral responsibility. The research employs a qualitative approach using library research, analyzing various sources such as academic books, scholarly journals, and relevant documents. The findings indicate that the application of objectivity in assessment minimizes subjective bias, while fairness ensures equal treatment and opportunities for all students. Moreover, honesty serves as the foundation for maintaining integrity in the assessment process, both for educators and learners. Therefore, the implementation of ethical principles in evaluation not only enhances the validity and reliability of assessment results but also contributes to the development of students’ character and academic integrity. In conclusion, ethical evaluation must be consistently applied to create a transparent, accountable, and high-quality educational assessment system.